KEMAMPUAN MENGONVERSI TEKS CERITA RAKYAT MENJADI NASKAH DRAMA OLEH SISWA KELAS XI BAHASA SMAN 1 TAEBENU BAUMATA KUPANG - Topo, Lidwina; Robot, Marselus; Margareta, Karus M. (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
This thesis written by Lidwina Mariana Topo with the title “The Ability to Convert Foklore Texts Into Drama Script by Class XI Language SMAN 1 Taebenu Baumata Kupang”. Supervisior by Dr. Marselus Robot, M.Si. and Dra. Karus M. Margareta, M.Pd. The main problem in this research is how is the ability of class XI Language SMAN 1 Taebenu Kupang Baumata Kupang students in converting folklore text into a drama script? The purpose of this research is to datermince the students’ ability in converting a folk tale text into a drama script. In this research, the reseacher conducted a performance test on students of class XI Language SMAN 1 Taebenu Baumata Kupang, as research subjects with a total of 19 research subjects.Reseachers will collect data which will then be analyzed based on the aspect of the assessment of drama script. This type of research is a qualitative descriptive, because the data collected will be analyzed as a category of words not numbers. The result showed: (1) Students skills in converting folklore texts into drama scripts There are 9 or 47% of students successful obtainingcompleteness when converting a drama script from a folk tale; (2) Then the average ability ofclass Language SMAN 1 Taebenu Baumata Kupang is 62,8. Thus, it can be concluded that theability to convert folklore texts into drama scripts in class Language SMAN 1 Taebenu Baumata Kupang is still in the poor category and still needs a lot of practice to be able to writw/convert, especially writing a drama script.